Equilibrium Studies on Binary and Ternary Complexes of Transition Metal Ions Containing Substituted Pyrimidines - Ravinder Reddy, V.; Reddy, K.Venugopal (Asian Journal of Chemistry, 2010)
Equilibrium studies on the formation of binary MA and ternary MAL complexes [where M = Co(II), Ni(II), Cu(II) and Zn(II); A = orotic acid (OA) and isoorotic acid (IOA); L = alanine (ala) phenylalanine (phala) tryptophan (trypt) 2,2'-bipyridyl (bipy) and o-phenanthroline (ophen)] have been carried out in aqueous medium using pH-metric technique at 25, 35, 45 ± 1ºC and 0.1 M (KNO3) ionic strength. All metal ions were formed 1 : 1 and 1 : 1 : 1 ternary complexes. The thermodynamic parameters ΔHfº, ΔGfº, ΔSfº, associated with binary and ternary complex systems were calculated and discussed. The relative stabilities of ternary complexes are quantitatively expressed in terms of the statistical parameter Δlog K. The results were discussed in the light of the basicity of ligands, statistical aspects, electrostatic interactions, denticity, stacking interactions, nature of donor sites and stereochemical aspects. The concentration profiles have indicated the favourability of the formation of binary and ternary complexes in general as reflected in the Δlog K values.